A retrospective analysis of factors used to assess fitness to stand trial in adult male defendants referred for psychiatric observation - Jacobson, Candice (Department of Psychiatry and Mental Health, 2017)
Background. A court orders a forensic observation of a defendant to determine a defendant's fitness to stand trial and/or ability to appreciate wrongfulness of action (criminal responsibility) at the time of the alleged offence. Fitness to stand trial is the focus of this review rather than criminal responsibility. In this instance, the court requests an expert to determine whether the defendant's current mental state would significantly impair his or her ability to participate meaningfully in his or her own trial. In South Africa, this process involves multiple assessments by a multidisciplinary forensic psychiatry team in a dedicated forensic psychiatry unit. However, at present no standardised format has been adopted for such an evaluation, the findings of which may have dire consequences for the individual being assessed. Furthermore, there is a paucity of current literature on fitness to stand trial evaluation. Objectives. To establish whether fitness to stand trial is adequately assessed in the Western Cape, South Africa. A further objective is to establish whether mental illness is the sole factor that differentiates defendants fit to stand trial from those who are found not fit to stand trial, and whether defendants with mental illness are less likely to be asked the relevant questions to determine fitness to stand trial than those without mental illness. Methods. A descriptive, retrospective review was conducted (via the application of a checklist) of clinical records of the last 100 male defendants' ≥18 years of age admitted to the Valkenberg Hospital Forensic Psychiatry Unit prior to March 2015. Results. 30 defendants (30%) were found to have a psychiatric diagnosis. Of the 30 defendants, all were noted to have a serious mental illness (mostly psychotic disorder or cognitive impairment) and were found not fit to stand trial. Seventy (70%) of the defendants were found fit to stand trial by the expert panel. From the findings, it was noted that the forensic team asked and recorded the necessary factors to determine fitness to stand trial in 56% of the study population (based on frequency of responses: n = 894), with 32% of questions not appearing to have been addressed at all (especially those pertaining to role players in court and a defendant's understanding of his rights). Furthermore, various questions appeared to have been indirectly addressed in fewer than 50% of defendants. No significant difference was noted in how the forensic team conducted its assessments between those defendants found to have a serious mental illness and those without serious mental illness. Conclusion. The results of the study suggest the need for a more in-depth review of the forensic evaluation process in the Western Cape to further ascertain the benefits of using a checklist during the evaluation process. Furthermore, additional research would assist in determining the factors contributing to a number of questions not having been addressed and the consequences thereof.